To Med or Not to Med: Factors Affecting Career Choice among Filipino Third-Year Medical Technology Students - De Guzman, Krista; Basa, Vince Lennon; Borromeo, Rykeil; De Villa, Gwyneth Kaye; Lacson, Raya Isidora; Nepomuceno, Anne Julia (International Journal of Arts, Sciences and Education, 2021)
In the Philippines, there has been an observable trend of students enrolling in Medical Technology with the intention of taking it as a pre-medical program instead of a professional program. This led the researchers to wonder what possible factors could have contributed to making that choice. The study sought to describe the respondents based on their demographic profile and determine their proportion based on their career paths. It will also evaluate and correlate the factors that affect the choice of Filipino third-year medical technology students in a university in Manila, Philippines and determine what is the least and most significant factor that affects the respondents. This is a quantitative study that uses a survey questionnaire conducted online. The researchers utilized a stratified random sampling technique to select 274 participants using the Raosoft Sample Size Calculator. Statistical analysis of the collected data involved mean and percentage, and the use of chi-square test to demonstrate any relationship between the different factors. Viable participants in the study were asked to accomplish a consent form. Results showed that the majority of the respondents (90.15%) have plans to pursue medical school. Moreover, individual-related factors have an impact on the decision of students to work in the Philippines and to work abroad. Social-related factors are taken into consideration by the students who plan to work abroad while competencies-related factors affect the decision of the students to proceed to medical school. In addition, the most significant factors affecting the career choice of the respondents are competencies-related (overall weighted mean = 4.126, agree) while the least significant factors are family-related (overall weighted mean = 2.626, neutral).